Numerical simulation of tangential flow flameless combustion process - Hamidi, Ehsan (2014)
Rapid industrialization and changes in life style cause a teremendous increase in energy consumption. Fossil fuels are the most common energy source in the world. Increasing of fuel consumption cuased more pollutant formation and resources depletion. In this project flameless combustion has been investigated as a reliable solution to this problem. Many studies has been carried out on different setup of flameless burners. In this thesis a new setup has been studied that is tangential fuel-oxidizer arrangement of inlets. This study shows that changing in the arrangement of inlets from co-axial to tangential will increase the efficiency of the lab scale combustor upto 14% and caused reduction of emissions and in particular NOx formation upto 55%. Also it has been concluded that the maximum temperature of flameless combustion in this new setting is higher by about 12%. Additionally this maximum temperature occurs near the wall of the combustor despite of co-axial flow which its highest temperature occurs at the center line. This phenomena helps improving of combustion efficiency. Because the most application of this kind of burners are in the boilers and the pipes which carry water to be heated are installed near the wall of boilers this issue can be considered as a big advantages of tangential flow flameless combustion process rather than co-axial one